류마티스 관절염 환자에서 발생한 신경병성 관절병증의 수술적 접근: 증례 보고 - 유현규; 김재원; 이성현; Hyunkyu Yu; Jaewon Kim; Sunghyun Lee (대한족부족관절학회지, 2024)
Neuropathic arthropathy (Charcot arthropathy) is a progressive joint disease often associated with conditions such as diabetes, leading to severe joint deformity and pain. However, its occurrence in patients with rheumatoid arthritis (RA) is rare and not well documented. This case report describes a 48-year-old woman with a long history of RA who developed a severe deformity of her right ankle, identified as neuropathic arthropathy extending to the subtalar joint (Brodsky classification type 3A). After excluding other potential causes, the condition was determined to be secondary to RA-associated peripheral neuropathy. Surgery, including allograft and autograft fixation, was performed to correct the deformity. Post-operative complications, such as wound infection, were treated with negative pressure wound therapy and skin grafting. At the 18-month follow-up, the patient was able to walk without pain, demonstrating successful joint fusion.